A Comprehensive Literature Analysis of the Implementation of the Merdeka Curriculum and Its Impact on Learning Innovation Across Educational Levels - Supri Hartini; Amir Mashruhim; Laili Komariyah; Abdunnur (Al-Qalam Institue, 2026)
Education serves as a foundational pillar in developing learners’ potentials to become individuals who are faithful, ethical, competent, creative, and responsible, as mandated by Indonesia’s Law No. 20 of 2003. In response to evolving educational needs, the curriculum has continuously undergone reforms, culminating in the introduction of the Merdeka Curriculum. This curriculum emphasizes student-centered learning, flexibility, and the strengthening of the Profil Pelajar Pancasila. This study aims to analyze how the implementation of the Merdeka Curriculum across various educational levels influences learning innovation. Using a literature review approach, the study synthesized findings from national and international publications focusing on curriculum reform, project-based learning, teacher competency development, and the Merdeka Belajar Kampus Merdeka (MBKM) policy in higher education. The review indicates that the Merdeka Curriculum has encouraged notable improvements in educators’ pedagogical competencie